Systematic review on the role of the gut microbiota in tumors and their treatment - Shi, Ying; Li, Xiao; Zhang, Jin (Frontiers in Endocrinology, 2024)
Tumors present a formidable health risk with limited curability and high mortality; existing treatments face challenges in addressing the unique tumor microenvironment (hypoxia, low pH, and high permeability), necessitating the development of new therapeutic approaches. Under certain circumstances, certain bacteria, especially anaerobes or parthenogenetic anaerobes, accumulate and proliferate in the tumor environment. This phenomenon activates a series of responses in the body that ultimately produce anti-tumor effects. These bacteria can target and colonize the tumor microenvironment, promoting responses aimed at targeting and fighting tumor cells.Understanding and exploiting such interactions holds promise for innovative therapeutic strategies, potentially augmenting existing treatments and contributing to the development of more effective and targeted approaches to fighting tumors. This paper reviews the tumor-promoting mechanisms and anti-tumor effects of the digestive tract microbiome and describes bacterial therapeutic strategies for tumors, including natural and engineered anti-tumor strategies.